HE ROLE OF PUZZLE PLAYING ACTIVITIES ON THE INVESTMENT OF RELIGIOUS MORAL VALUE IN GROUP B TK AL-KHAIRAAT TAIPA KELURAHAN TAIPA KECAMATAN PALU UTARA PALU CITY - Hasria Hasria; Nurhayati Nurhayati (Universitas Tadulako, 2020)
The research objectives were to determine the introduction of children in the cultivation of religious moral values, to determine the application of play activities, and to determine whether there was an effect of playing activities on the cultivation of religious moral values ​​in group B of Al-Khairaat Taipa Kindergarten, Taipa Village, North Palu District, Palu City. The formulation of the problem in the research is how to introduce children to the cultivation of religious moral values, how to implement play activities, and whether there is an effect of playing activities on the cultivation of religious moral values ​​in group B of Al-Khairaat Taipa Kindergarten, Taipa Village, North Palu District, Palu City. The research method used is a quantitative method with this type of research is experimental. The research subjects were 15 children. Data were collected through observation and documentation sheets. The data collection technique is done by using percentage technique and T-test. This is from the descriptive analysis, before being given the average value of the development of children's religious moral values, there were no children in the BSB category, 20% children in the BSH category, 26.67% children in the MB category and 53 children, 33% in the BB category. Furthermore, after being given treatment, the average value of the development of children's religious moral values ​​was 25% in the BSB category, 44.46% in the BSH category, 30 MB categories, and none in the BB category. Meanwhile, from the t test it can be explained that the t value is 18,500 with a significant 0,000. Because sig <0.05, it can be concluded that H0 is rejected and H1 is accepted, therefore, it can be concluded that playing puzzles has a significant effect on children's religious moral values